2004
DOI: 10.1002/jemt.20120
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study on human placenta from intrauterine growth retardation cases

Abstract: A morphological study was performed on 27 human placentas from normal gestations (Group 1) and compared with those from eight cases of intrauterine growth restriction (IUGR) (Group 2). Semithin section light microscopy, transmission, and scanning electron microscopy were carried out on trophoblastic terminal villi, carefully identified under the stereomicroscope. In growth retardation cases, villi appear longer, thinner, and less vascularized, compared to the normal condition. Fibrinoid, an extracellular mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Similar to the findings with high doses of AS 4.5 used in this study, Battistelli et al [3] have described some thickening of subtrophoblastic basal laminae and extracellular fibrosis within the villous stroma in cases of FGR. They attributed the stromal fibrosis to excess fibrinoid, formed in part as a coagulation product.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to the findings with high doses of AS 4.5 used in this study, Battistelli et al [3] have described some thickening of subtrophoblastic basal laminae and extracellular fibrosis within the villous stroma in cases of FGR. They attributed the stromal fibrosis to excess fibrinoid, formed in part as a coagulation product.…”
Section: Discussionsupporting
confidence: 84%
“…In women with a history of FGR, approximately 60%-70% of cases are associated with some form of maternal thrombophilia, of which hyperhomocysteinemia, factor V Leiden, and acquired activated protein C resistance are the conditions most commonly diagnosed [2]. In addition to the high incidence of thrombophilic disorders, FGR is also characterized by excessive placental perivillous fibrinoid, often filling the villous stroma [3], and reduced villous growth [4], resulting in overall placental insufficiency. During normal placental development, this fibrin/fibrinoid turnover is a continuous and tightly regulated process [5] that mediates the formation of villous trees [6].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, cytotrophoblastic cells showed abnormal orientation, reduction in size and density of microvilli. The decreased microvillus density observed in the current study has also been reported in other complications such as IUGR placentae [25] and preeclampsia. [17] In the rat, cytotrophoblasts continuously differentiate into ST during villous formation and development and are important in invasion of blood vessels remodeling in early stages of implantation.…”
Section: Discussionsupporting
confidence: 87%
“…Proteins of the exocyst complex have never been studied in the placenta, but may be important in maintenance of the microvilli and the apical plasma membrane of the STB. It has been reported that the STB of placentas from pregnancies complicated by intrauterine growth restriction (IUGR) have less elaborate microvilli that in normal placentas [31]. It is interesting to speculate that that expression of exocyst complex proteins may be modulated in IUGR.…”
Section: Discussionmentioning
confidence: 99%